Teleoperation of Multi-Degrees-of-Freedom Manipulator through Composite State Convergence Scheme. Issue 1 (2022) - Asad, Muhammad Usman; Gu, Jason; Farooq, Umar; Dey, Rajeeb; Balas, Valentina E.; Abbas, Ghulam
Abstract: In this paper, design of composite state convergence controller for teleoperating a multi-degrees-of-freedom manipulator is presented. The composite variables corresponding to the joints of the master and slave manipulators as well as operator's force are transmitted across the communication channel. The control laws for the master and slave systems are defined according to the composite state convergence scheme with the addition of cancellation terms containing the nonlinear dynamics of master and slave manipulators. It is shown that convergence of composite variables of respective master and slave joints guarantee the convergence of respective joint positions of the master and slave systems under the composite state convergence control laws. MATLAB simulations on time-delayed teleoperation model are performed to validate the proposal.